Treatment by glyphosate-based herbicide allowed recovering native species after Oxalis pes-caprae L. invasion: indications from a Mediterranean island. (3rd September 2019) - Lazzaro, Lorenzo; Ferretti, Giulio; Bianchi, Elisabetta; Benesperi, Renato
Abstract: Biological invasions represent a global threat to biodiversity. Particular attention should be devoted to the management of alien plants, focusing on the opportunity to obtain a rapid response to invasion and restoration of the invaded areas. In this study we aimed to evaluate five different methods for controlling Oxali s pes-caprae, a well-known invasive plant native to South Africa, also focusing on the restoration of the native flora. We set an experiment on the island of Montecristo (central Mediterranean). Treatment methods varied from chemical to low risk methods, including manual removal, covering with mulching sheets, and foliar spraying with acetic acid (30% solution) and two different concentrations of glyphosate (3 and 5% solutions, respectively). The total cover of O. pes-caprae and of other native plants was sampled before treatments, and then several times during the subsequent year; while the plant species composition was sampled in late winter (March 2015–2016) and late spring (May 2015–2016). The use of glyphosate was found to be the only efficient control method, leading to a significant decrease in O. pes-caprae cover as well as to a recovery in native species cover and richness. The effect of the other control methods was negligible.